2001
DOI: 10.1007/s11926-001-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of gender in fibromyalgia syndrome

Abstract: Fibromyalgia syndrome (FMS), characterized by widespread pain and tenderness on palpation (tender points), is much more common in women than in men in a proportion of 9:1. Two recent studies have shown important gender differences in various clinical characteristics of FMS. In a community and a clinic sample, women experienced significantly more common fatigue, morning fatigue, hurt all over, total number of symptoms, and irritable bowel syndrome. Women had significantly more tender points. Pain severity, glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
78
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 44 publications
(46 reference statements)
8
78
0
5
Order By: Relevance
“…Another study showed that husbands of women with FM had a high prevalence of FM . This is intriguing, because the prevalence of FM in men is substantially lower than in women (Yunus 2001;Yunus 2002) and, more importantly, because familial or environmental influences would be implicated in this association, rather than genetic ones.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that husbands of women with FM had a high prevalence of FM . This is intriguing, because the prevalence of FM in men is substantially lower than in women (Yunus 2001;Yunus 2002) and, more importantly, because familial or environmental influences would be implicated in this association, rather than genetic ones.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that husbands of women with FM had a high prevalence of FM . This is intriguing, because the prevalence of FM in men is substantially lower than in women (Yunus, 2001 and, more importantly, because familial or environmental influences would be implicated in this association, rather than genetic ones.…”
Section: Discussionmentioning
confidence: 99%
“…COMUNICAÇÃO SAÚDE EDUCAÇÃO 2016; 20(56): [25][26][27][28][29][30][31][32][33][34][35][36] También en este caso observamos que la referencia a la psicología se hace sin distinguir o definir las áreas de implicancia, corriente teórica o la especialidad a la que se refiere, a diferencia de lo que sucede con respecto a las disciplinas biomédicas.…”
Section: E Disciplinaunclassified
“…Las cuestiones referidas al género han sido tenido en cuenta por algunos autores 34 , quienes explican a partir de factores biológicos -mutaciones genéticas, alteraciones en mecanismos sensoriales, psicológicos -que las mujeres reportan más distrés psicológico que los hombres -y socioculturales -estereotipos de los roles. Sin embargo, otros trabajos 35 plantearon que estas diferencias pueden deberse a sesgos de los profesionales que diagnostican, lo cual cuestionaría -y plantearía la necesidad de revisar -estas diferencias en la prevalencia.…”
Section: E Disciplinaunclassified